The Effect of Health Coaching on Behavior Changed to Prevent Hypertension among Adolescents in High School of Wangiapu City, East Sumba - ester radandima; Oedojo Soedirham; Retno Indarwati (International Journal of Nursing and Health Services (IJNHS), 2020)
Adolescents play an important role as a determinant of the future of a nation, because of that, adolescents have to attention about their health. The phenomenon showed many adolescents were at risk in early hypertension. The study aimed to examine the effect of health coaching on behavior changes to prevent hypertension among adolescents in Senior High School Waingapu City, East Sumba. A quasi-experimental study design, pre and post-test, with an equivalent control group was applied in this study. We select samples using a simple random sampling for 29 experimental groups and 29 samples in the control group. The results of the study will be analyzed using the Wilcoxon Signed Ranks Test with P <0.05. The results showed a positive effect of health coaching on behavior change based on the theory of Health Promotion Model, such us in perceived benefit of action (p=0.000), perceived barrier to action (p=0.004), perceived self-efficacy (p=0.003), activity-related effect (p=0.002), commitment (p=0.000) and behavior change in adolescents to prevent hypertension (p=0.096). Health coaching can be applied in changing adolescent behavior to prevent hypertension. Coaching and training needed to change not just knowledge occur, but also attitudes, actions, and commitments from adolescents